Sistem Diagnosis Penyakit Ikan Koi Menggunakan Metode Forward Chaining dan Dempster-Shafer - Mohammad Zahrul Muttaqin; Edy Santoso; Bayu Rahayudi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Cultivator's knowledge about what kind of diseases that can infected by Koi at the time of cultivation was very less. Disease predicted indication on Koi cultivation is an important thing to the success of cultivation. Disease prediction obtained by the facts that exist on the cultivation process. Disease determination of Koi can be a source of insufficient information. So that required applications that have knowledge such as experts (specialist). Forward Chaining and Dempster-shafer is a mathematical theory for evidence based on belief functions and plausible reasoning, used to combine separate pieces of information (evidence) to calculate the probability of an event. The method used to get the diagnosis by sorting between general and special symptoms. This application is expected to perform diagnosis and provide ways of handling such as what experts gonna do. In this research, measured accuracy level of application is 95%.